José de Souza Martins' intelligentsia and other agrarian issues - Costa da Fonseca, Bruno (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2021)
This article is intended to clarify part of the theoretical production of sociologist José de Souza Martins due to the discussion on the theme of the Agrarian Question in Brazilian Social Thought. In the classic conceptions of authors like Marx, Lenin and Kautsky, this debate was tied – to a certain extent – to the theme of the Socialist Revolution in European countries. In the Brazilian context, we have diversity around the pecebista, cepalino currents, the economic conservatism and the progressive Catholic Church, which Martins was sympathetic to. In Martins’ view, the Agrarian Question should be conceived from the emancipation of rural workers as of the expansion of capitalism in the countryside and radical land reform was never the immediate solution to the problems of the countryside. According to him, the conquest of the “land of work”, also the theme of the progressive Catholic Church in the 1980s, was more promising than the Marxist intervention proposed by the Communist Party.